Negative electrode material for lithium ion secondary battery and method for producing the same, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

By using a negative electrode material of multi-layer planar graphite particles and combined with a specific manufacturing process, the problem of difficult suppression of electrolyte decomposition reaction of lithium-ion secondary batteries at high temperatures is solved, and the high-temperature impedance and electrolyte injection properties are improved, extending the service life of the battery and improving the charge and discharge efficiency.

JP7666336B2Active Publication Date: 2025-04-22RESONAC CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021574368
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-01-30
Publication Date
2025-04-22
Estimated Expiration
2040-01-30

AI Technical Summary

Technical Problem

In the high temperature conditions of existing lithium-ion secondary batteries, the decomposition reaction of electrolytes is difficult to suppress, resulting in a decrease in battery capacity. In commercial vehicle applications, high temperature impedance and electrolyte injection properties are insufficient.

Method used

A negative electrode material with a structure of multi-layer planar graphite particles is adopted, and its particle size distribution D90/D10 is between 2.0 and 5.0, and has a high degree of patterning and an appropriate surface area. A low-crystalline carbon surface is formed through a specific manufacturing process to improve the high-temperature impedance and electrolyte implantability of the battery.

Benefits of technology

It significantly improves the high-temperature impedance and electrolyte injection properties of lithium-ion secondary batteries at high temperatures, extends the service life of the battery, and improves the efficiency of fast charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666336000002
    Figure 0007666336000002
  • Figure 0007666336000003
    Figure 0007666336000003
  • Figure 0007666336000004
    Figure 0007666336000004
Patent Text Reader

Abstract

A negative-electrode material for a lithium-ion secondary cell, the negative-electrode material containing composite particles having a structure in which a plurality of flat graphite particles are layered, and being such that the grain size distribution D90 / D10 of the composite particles is 2.0-5.0, or the grain size distribution D90 / D10 of the plurality of flat graphite particles is 2.0-4.4. 
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to a negative electrode material for a lithium ion secondary battery and a method for producing the same, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. [Background technology]

[0002] Lithium-ion secondary batteries, taking advantage of their small size, light weight, and high energy density, have been widely used in electronic devices such as notebook personal computers (PCs), mobile phones, smartphones, and tablet PCs. In recent years, environmental issues such as global warming due to CO2 emissions have led to the widespread use of clean electric vehicles (EVs) that run solely on batteries, hybrid electric vehicles (HEVs) that combine gasoline engines with batteries, and plug-in hybrid electric vehicles (PHEVs). Lithium-ion secondary batteries (automotive lithium-ion secondary batteries) are now being used in EVs, HEVs, PHEVs, and other vehicles. Recently, lithium-ion secondary batteries have also been used for power storage, and their applications are expanding to a wide range of fields.

[0003] The input characteristics of lithium-ion secondary batteries are significantly affected by the performance of their negative electrode materials. Carbon materials are widely used as negative electrode materials for lithium-ion secondary batteries. For example, highly crystalline carbon materials such as artificial graphite and spherical natural graphite, which is made by spheroidizing scaly natural graphite, have been proposed as materials for obtaining high-density negative electrodes.

[0004] As an example of artificial graphite, International Publication No. 2015 / 147012 discloses a negative electrode material for lithium ion secondary batteries containing composite particles including spherical graphite particles and a plurality of flat graphite particles aggregated or bonded so that their oriented planes are non-parallel. Japanese Patent Application Laid-Open No. 2005-302725 also discloses a negative electrode active material for lithium secondary batteries containing carbon powder particles having a morphology in which plate-like particles are oriented and stacked along their surfaces to form a primarily stable structure, and in which micropores are formed on the surface. Summary of the Invention [Problem to be solved by the invention]

[0005] In lithium-ion secondary batteries, exposure to high temperatures reduces the activation energy for electrolyte decomposition, making electrolyte decomposition by the negative electrode active material more likely to occur. Progression of the electrolyte decomposition reaction leads to a decrease in battery capacity due to consumption of the electrolyte, so it is desirable to suppress the decomposition of the electrolyte as much as possible. However, while conventional carbon materials have been improved in terms of capacity and cycle characteristics, there is still room for improvement in suppressing the electrolyte decomposition reaction during high-temperature storage.

[0006] In addition, commercial vehicles such as buses and delivery trucks have predictable driving distances, making them relatively easy to electrify. As these vehicles are expected to be driven mainly during the day, lithium-ion secondary batteries are required to have particularly excellent high-temperature resistance.

[0007] Furthermore, it was difficult with conventional technology to suppress the decomposition reaction of the electrolyte at the interface between the negative electrode material and the electrolyte while maintaining good circulation of the electrolyte and ensuring sufficient mobility of lithium ions.

[0008] In view of the above circumstances, an object of the present disclosure is to provide a negative electrode material for lithium ion secondary batteries that can be used to fabricate lithium ion secondary batteries that have excellent high-temperature resistance and excellent electrolyte injection properties, a method for manufacturing the same, and a negative electrode for lithium ion secondary batteries and a lithium ion secondary battery fabricated using the negative electrode material. [Means for solving the problem]

[0009] Means for solving the above problems include the following aspects. <1> A negative electrode material for a lithium ion secondary battery, comprising composite particles having a structure in which a plurality of flaky graphite particles are stacked, the particle size distribution D90 / D10 of the composite particles being 2.0 to 5.0. <2> A negative electrode material for a lithium ion secondary battery, comprising composite particles having a structure in which a plurality of flaky graphite particles are stacked, wherein the particle size distribution D90 / D10 of the plurality of flaky graphite particles is 2.0 to 4.4. <3> The particle size distribution D90 / D10 of the composite particles is 2.0 to 5.0. <2> The negative electrode material for a lithium ion secondary battery according to claim 1. <4> The specific surface area of ​​the composite particles determined by nitrogen adsorption measurement at 77 K is 0.5 m 2 / g~2.8m 2 / g, <1> ~ <3> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, wherein the negative electrode material is a lithium ion secondary battery material. <5> The degree of graphitization of the composite particles determined by X-ray diffraction is 93.0% to 98.0%. <1> ~ <4> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, wherein the negative electrode material is a lithium ion secondary battery material. <6> In the composite particles, in an X-ray diffraction pattern using CuKα radiation, the intensity ratio (P1 / P2) of the diffraction peak (P1) of the (101) plane of the rhombohedral crystal structure to the diffraction peak (P2) of the (101) plane of the hexagonal crystal structure is 0.15 or less. <1> ~ <5> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, wherein the negative electrode material is a lithium ion secondary battery material. <7> the composite particles have low-crystalline carbon disposed on at least a portion of the surface thereof, and the R value of the composite particles having low-crystalline carbon disposed thereon is 0.50 or less in Raman spectroscopy measurement; <1> ~ <6> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, wherein the negative electrode material is a lithium ion secondary battery material. <8> the composite particles are not provided with low-crystalline carbon on the surface thereof, and the R value of the composite particles not provided with low-crystalline carbon in Raman spectroscopy measurement is 0.20 or less. <1> ~ <6> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, wherein the negative electrode material is a lithium ion secondary battery material. <9> The oil absorption of the composite particles is 15 mL / 100 g to 45 mL / 100 g. <1> ~ <8> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, wherein the negative electrode material is a lithium ion secondary battery material. <10> The composite particles are mixed with a mixture of the composite particles and the mixture of the composite particles and the mixture of the composite particles. 3 After compressing it to a density of 1.8 g / cm, the pressure is released. 3 The absolute value of the difference between the density of the composite particles after pressure release and the density of the composite particles after pressure release was calculated as 1.8 g / cm3 The springback amount obtained by dividing by is 40% or more. <1> ~ <9> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, wherein the negative electrode material is a lithium ion secondary battery material. <11> <1> ~ <10> 10. A negative electrode for a lithium ion secondary battery, comprising: a negative electrode material layer containing the negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 9; and a current collector. <12> <11> A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to claim 1, a positive electrode, and an electrolyte solution. <13> classifying the plurality of flat graphitizable aggregates to remove at least one selected from the group consisting of fine particles and coarse particles; mixing the classified flat graphitizable aggregates with a binder to obtain a mixture; processing the mixture to produce secondary particles having a structure in which the plurality of flat graphitizable aggregates are stacked; a step of graphitizing the secondary particles to obtain composite particles having a structure in which a plurality of flat graphite particles are stacked; classifying the composite particles to remove at least one selected from the group consisting of fine particles and coarse particles; A method for producing a negative electrode material for a lithium ion secondary battery, comprising: <14> The negative electrode material for lithium ion secondary batteries is <1> ~ <10> The negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 10, <13> A method for producing the negative electrode material for a lithium ion secondary battery according to claim 1. <15> The particle size distribution D90 / D10 of the flat graphitizable aggregate is 2.0 to 4.4. <13> or <14> A method for producing the negative electrode material for a lithium ion secondary battery according to claim 1. <16> The bulk density of the secondary particles to be graphitized is 0.4 g / cm 3 ~1.0g / cm 3 That is, <13> ~ <15> 10. A method for producing the negative electrode material for a lithium ion secondary battery according to claim 9. <17> processing the mixture includes heating the mixture to volatilize volatile components of the binder; <13> ~ <16> 10. A method for producing the negative electrode material for a lithium ion secondary battery according to claim 9. <18> The pressure in the atmosphere is reduced during the heating. <17> A method for producing the negative electrode material for a lithium ion secondary battery according to claim 1. [Effects of the Invention]

[0010] According to the present disclosure, there are provided a negative electrode material for lithium ion secondary batteries that can produce lithium ion secondary batteries that have excellent high-temperature resistance and excellent electrolyte injection properties, a method for producing the same, and a negative electrode for lithium ion secondary batteries and a lithium ion secondary battery produced using the negative electrode material. [Brief explanation of the drawings]

[0011] [Figure 1A] 1 shows an electron microscope photograph of the negative electrode material of Example 1. [Figure 1B] 1 shows an electron microscope photograph of a cross section of the negative electrode material of Example 1. [Figure 2A] 1 shows an electron microscope photograph of the negative electrode material of Comparative Example 1. [Figure 2B] 1 shows an electron microscope photograph of a cross section of the negative electrode material of Comparative Example 1. [Figure 3A] 1 shows an electron microscope photograph of the negative electrode material of Comparative Example 2. [Figure 3B] 1 shows an electron microscope photograph of a cross section of the negative electrode material of Comparative Example 2. [Figure 4A] 1 shows an electron microscope photograph of the negative electrode material of Comparative Example 3. [Figure 4B] 1 shows an electron microscope photograph of a cross section of the negative electrode material of Comparative Example 3. DETAILED DESCRIPTION OF THE INVENTION

[0012] Hereinafter, embodiments for carrying out the present invention will be described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, components (including element steps, etc.) are not essential unless otherwise specified. The same applies to numerical values ​​and their ranges, and do not limit the present invention.

[0013] In the present disclosure, the term "process" includes not only a process that is independent of other processes, but also a process that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved. In the present disclosure, numerical ranges indicated using "to" include the numerical values ​​before and after "to" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this disclosure, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. Furthermore, in the numerical ranges described in this disclosure, the upper or lower limit value of that numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple substances corresponding to the component. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, multiple types of particles corresponding to each component may be contained. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified. In the present disclosure, the terms "layer" and "film" include cases where the layer or film is formed over the entire area when the area in which the layer or film is present is observed, as well as cases where the layer or film is formed over only a portion of the area. In this disclosure, the term "lamination" refers to stacking layers, and two or more layers may be bonded together, or two or more layers may be detachable.

[0014] In the present disclosure, the particle size distribution of the negative electrode material and the primary particles contained in the composite particles can be measured using a laser diffraction particle size distribution analyzer. The average particle size of the particles is the particle size (D50) at which the cumulative total from the small diameter side in the volume-based particle size distribution is 50%. D90 is the particle size at which the cumulative total from the small diameter side in the volume-based particle size distribution is 90%, and D10 is the particle size at which the cumulative total from the small diameter side in the volume-based particle size distribution is 10%.

[0015] <Anode material for lithium-ion secondary batteries> The negative electrode material for lithium ion secondary batteries in the first embodiment of the present disclosure includes composite particles having a structure in which a plurality of flaky graphite particles are stacked, and the particle size distribution D90 / D10 of the composite particles is 2.0 to 5.0.

[0016] The negative electrode material according to the first embodiment of the present disclosure enables the fabrication of a lithium-ion secondary battery that exhibits excellent high-temperature resistance and excellent electrolyte injectability. The reason for this is not entirely clear, but it can be considered as follows. The negative electrode material according to the first embodiment of the present disclosure includes specific composite particles having a structure in which a plurality of flaky graphite particles are stacked. This stacked structure, when used as a negative electrode material, is thought to reduce the number of interfaces with the electrolyte inside the specific composite particles compared to the negative electrode material described in, for example, International Publication No. 2015 / 147012, thereby suppressing decomposition of the electrolyte even at high temperatures. Furthermore, the presence of this stacked structure is thought to prevent the particles from being crushed even when pressure is applied during the fabrication of the negative electrode, and thus less likely to obstruct the passage of the electrolyte. This is thought to enable favorable electrolyte injectability to be maintained. Furthermore, in the negative electrode material according to the first embodiment of the present disclosure, the particle size distribution D90 / D10 of the specific composite particles is 2.0 to 5.0. Although the specific composite particles have a relatively small amount of pores inside, the particle size distribution D90 / D10 of the specific composite particles is 2.0 to 5.0, and the particle size variation is relatively small, which is thought to enable the interparticle voids to maintain a good path for the electrolyte.

[0017] The negative electrode material for a lithium ion secondary battery according to the second embodiment of the present disclosure includes composite particles having a structure in which a plurality of flaky graphite particles are stacked, and the particle size distribution D90 / D10 of the plurality of flaky graphite particles is 2.0 to 4.4.

[0018] The negative electrode material according to the second embodiment of the present disclosure enables the fabrication of a lithium-ion secondary battery that is excellent in high-temperature resistance and electrolyte injectability. The reason for this is not entirely clear, but it can be considered as follows. The negative electrode material according to the second embodiment of the present disclosure includes specific composite particles having a structure in which a plurality of flaky graphite particles are stacked. This stacked structure, when used as a negative electrode material, is thought to reduce the number of interfaces with the electrolyte inside the specific composite particles, compared to the negative electrode material described in, for example, WO 2015 / 147012, thereby suppressing decomposition of the electrolyte even at high temperatures. Furthermore, the presence of this stacked structure is thought to prevent the particles from being crushed even when pressure is applied during the fabrication of the negative electrode, and thus less likely to obstruct the passage of the electrolyte. This is thought to enable favorable electrolyte injectability to be maintained. Furthermore, in the negative electrode material according to the second embodiment of the present disclosure, the particle size distribution D90 / D10 of the plurality of flaky graphite particles (i.e., primary particles) is 2.0 to 4.4. The relatively uniform particle size of the multiple flaky graphite particles allows for the formation of a favorable laminated structure, reducing the amount of pores within the composite particles and the specific surface area. This is thought to suppress decomposition of the electrolyte and provide better high-temperature resistance. Furthermore, since particles with a relatively uniform laminated structure and relatively high hardness, i.e., elasticity, are obtained, it is thought that the particle shape is easily restored, i.e., springback, even when pressure is applied during the production of the negative electrode. As a result, it is thought that the electrolyte path can be well maintained when the battery is formed, further improving the injectability.

[0019] Hereinafter, the negative electrode materials for lithium ion secondary batteries according to the first and second embodiments of the present disclosure may be collectively referred to as "the negative electrode material of the present disclosure" or "the negative electrode material." Furthermore, composite particles having a structure in which a plurality of flaky graphite particles are stacked are sometimes referred to as "specific composite particles."

[0020] It has also been found that the negative electrode material for lithium-ion secondary batteries of the present disclosure inhibits the deposition of metallic lithium on the negative electrode during charging. Although the reason for this is unclear, it is speculated that one factor is that the electrolyte path is well maintained, making it easier for lithium ions to migrate to the positive electrode rather than remaining in the negative electrode.

[0021] The negative electrode material of the present disclosure may or may not contain particles other than the specific composite particles. That is, the negative electrode material of the present disclosure may consist essentially of the specific composite particles alone, or may be a mixture of the specific composite particles and other particles. Here, "consisting essentially of the specific composite particles alone" means that even if the negative electrode material contains a small amount of particles other than the specific composite particles (for example, 5% by mass or less, preferably 3% by mass or less of the total negative electrode material), the amount does not practically affect the battery characteristics.

[0022] Examples of particles other than the specific composite particles include negative electrode materials other than the specific composite particles, conductive additives, and the like. Examples of negative electrode materials other than the specific composite particles include natural graphite, artificial graphite, amorphous coated graphite, resin coated graphite, amorphous carbon, and occluded metal particles. Examples of the conductive additive include carbon black, graphite, acetylene black, oxides that exhibit conductivity, and nitrides that exhibit conductivity.

[0023] When the negative electrode material is a mixture of specific composite particles and particles other than the specific composite particles, the proportion of the specific composite particles to the total amount of the negative electrode material may be 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more, or may be 90% by mass or less.

[0024] [Specified composite particles] The specific composite particles have a structure in which a plurality of flat graphite particles are laminated (ie, stacked). The flat graphite particles refer to non-spherical graphite particles having anisotropic shapes, and examples of the flat graphite particles include graphite particles having a scaly, flake, or partially lumpy shape. Composite particles refer to particles in a state in which primary particles are aggregated or bonded together. That is, the specific composite particles have a structure in which a plurality of flaky graphite particles are stacked and aggregated or bonded together with their main surfaces facing each other. Therefore, a plurality of flaky graphite particles are stacked in a substantially parallel state to form a composite particle. Whether or not the flaky graphite particles are stacked can be confirmed by microscopic observation.

[0025] The state in which multiple flaky graphite particles are aggregated or bonded refers to a state in which two or more flaky graphite particles are aggregated or bonded. Bonding refers to a state in which the particles are chemically bonded to each other directly or via a carbon substance. Aggregation refers to a state in which the particles are not chemically bonded to each other but maintain the shape of an aggregate due to their shape, etc. The flaky graphite particles may be aggregated or bonded via a carbon substance. Examples of the carbon substance include graphite obtained by graphitizing an organic binder such as tar or pitch. Whether the flaky graphite particles are aggregated or bonded can be confirmed, for example, by observation using a scanning electron microscope.

[0026] The flaky graphite particles and their raw materials are not particularly limited, and examples thereof include artificial graphite, scaly natural graphite, scaly natural graphite, coke, resin, etc. Among these, artificial graphite is preferred from the viewpoints of its resistance to deformation and its low specific surface area. When natural graphite is used as part of the raw material, the proportion of natural graphite in the specific composite particles is preferably 40% by mass or less from the viewpoints of its resistance to spheroidization and its ease of obtaining a layered structure.

[0027] The average particle size of the flaky graphite particles that make up the specific composite particles is, for example, preferably 5 μm to 25 μm, more preferably 8 μm to 20 μm, and even more preferably 10 μm to 15 μm, from the viewpoint of ease of aggregation or bonding. The average particle size of the flaky graphite particles can be determined by any of the following methods. The average particle size of the flat graphitizable aggregate described below that serves as the raw material for the specific composite particles, i.e., the particle size (D50) at which the cumulative total from the small diameter side in the volume-based particle size distribution reaches 50%, can be considered to be the average particle size of the flat graphite particles that make up the specific composite particles. The average particle size of the flaky graphite particles may be determined by observing the cross section of the specific composite particle under a scanning electron microscope and calculating the median particle size of 100 randomly selected flaky graphite particles. In this case, the particle size of each flaky graphite particle is defined as the equivalent circle diameter, which is the diameter of a circle having the same area as the projected area.

[0028] The particle size distribution D90 / D10 of the flaky graphite particles is preferably 4.4 or less, more preferably 4.0 or less, and even more preferably 3.5 or less. When the particle size distribution D90 / D10 of the flaky graphite particles is 4.4 or less, high temperature resistance and pourability tend to be further improved. From the viewpoint of reducing production costs, the particle size distribution D90 / D10 of the flaky graphite particles may be 2.0 or more. From the above viewpoints, the particle size distribution D90 / D10 of the flaky graphite particles is preferably 2.0 to 4.4, more preferably 2.0 to 4.0, and even more preferably 2.0 to 3.5. In the negative electrode material according to the second embodiment, the particle size distribution D90 / D10 of the flaky graphite particles is 2.0 to 4.4. The particle size distribution D90 / D10 of the flaky graphite particles can be determined by any of the following methods. The particle size distribution D90 / D10 obtained by measuring the flat graphitizable aggregate described below, which is the raw material for the specific composite particles, using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation) can be considered to be the particle size distribution D90 / D10 of the flat graphite particles that make up the specific composite particles. The particle size distribution D90 / D10 of the flaky graphite particles can be determined by observing the cross section of the specific composite particle with a scanning electron microscope, and calculating the ratio of the particle size (D90) at which the cumulative number of particles from the small diameter side of any 1,000 flaky graphite particles is 90% to the particle size (D10) at which the cumulative number of particles from the small diameter side is 10%. In this case, the particle size of each flaky graphite particle is defined as the equivalent circle diameter, which is the diameter of a circle having the same area as the projected area.

[0029] The aspect ratio of the flaky graphite particles, expressed as A / B, where A is the length in the major axis direction and B is the length in the minor axis direction, is preferably 2 to 20, and more preferably 4 to 10. An aspect ratio of 2 or more increases the external surface area, which reduces the buoyancy and tends to cause the particles to aggregate. When the particles aggregate, the major axis faces are stacked together to reduce the external surface area, maximizing the adhesion area between the particles. The van der Waals forces acting between the particles also contribute to stronger adhesion and stabilization. An aspect ratio of 20 or less tends to further improve the input / output characteristics, such as the rapid charge / discharge characteristics, of lithium-ion secondary batteries. Furthermore, an aspect ratio of 20 or less tends to thin each flaky graphite particle, increasing the number of layers, increasing the gaps within the particles and increasing the specific surface area, which tends to suppress a deterioration in storage characteristics.

[0030] The aspect ratio is determined by observing graphite particles under a microscope, randomly selecting 100 graphite particles, measuring the A / B ratio for each, and then calculating the arithmetic mean of these measurements. In observing the aspect ratio, the major axis length A and the minor axis length B are measured as follows. That is, in a projected image of a graphite particle observed under a microscope, two parallel tangents circumscribing the periphery of the graphite particle are selected, with tangents a1 and a2 having the greatest distance between them, and the major axis length A is defined as the distance between these tangents a1 and a2. In addition, two parallel tangents circumscribing the periphery of the graphite particle are selected, with tangents b1 and b2 having the smallest distance between them, and the minor axis length B is defined as the distance between these tangents b1 and b2.

[0031] The specific composite particles may have low-crystalline carbon disposed on at least a portion of the surface thereof. When low-crystalline carbon is disposed on at least a portion of the surface of the specific composite particles, the charging characteristics at low temperatures tend to be further improved when a lithium ion secondary battery is constructed from the specific composite particles. On the other hand, the specific composite particles may not have low-crystalline carbon disposed on their surfaces. If low-crystalline carbon is not disposed on the surfaces of the specific composite particles, cracking, peeling, etc., of the specific composite particles during pressing during electrode fabrication tends to be suppressed, which increases the decomposition activity of the electrolyte and reduces storage characteristics. This also has the advantage of allowing greater freedom in manufacturing conditions. It has been found that the negative electrode material disclosed herein tends to have excellent rapid input / output characteristics even when low-crystalline carbon is not disposed on the surface. This is thought to be because the rapid input / output characteristics are more significantly affected by the liquid circulation (and therefore the diffusion rate of solvated lithium) than by the surface structure of the specific composite particles.

[0032] "Low crystalline carbon" means carbon having an R value of 0.2 or more in a Raman spectrum.

[0033] The R value was measured by laser Raman spectroscopy at an excitation wavelength of 532 nm at 1360 cm -1 The intensity of the maximum peak appearing near Id is 1580 cm -1 When the intensity of the maximum peak that appears in the vicinity is Ig, the value is given as the intensity ratio Id / Ig of the two peaks. 1360cm -1 The peak appearing around 1300 cm is usually identified as corresponding to the amorphous structure of carbon, for example, -1 ~1400cm -1 Also, the peak observed at 1580 cm -1 The peak appearing around 1530 cm is usually identified as corresponding to the graphite crystal structure, for example, -1 ~1630cm -1 This refers to the peak observed at

[0034] The R value is measured using a Raman spectrometer (for example, NSR-1000 model manufactured by JASCO Corporation), and the spectrum obtained is measured under the following conditions with the following range as the baseline. Laser wavelength: 532nm Irradiation intensity: 1.5mW (measured by laser power monitor) Measurement range: 830cm -1 ~1940cm -1 Irradiation time: 60 seconds ·Irradiation area: 4μm 2 Baseline: 1050cm -1 ~1750cm -1

[0035] (Average particle size) From the viewpoint of further improving the permeability of the electrolyte solution, the average particle size of the specific composite particles is, for example, preferably 5 μm to 30 μm, more preferably 10 μm to 25 μm, and even more preferably 12 μm to 20 μm.

[0036] The average particle size of the specific composite particles can be measured using a laser diffraction particle size distribution analyzer (e.g., SALD3100, Shimadzu Corporation). The average particle size is the particle size (D50) at which the cumulative total from the small diameter side in the volume-based particle size distribution reaches 50%.

[0037] When an electrode (negative electrode) is manufactured using the negative electrode material of the present disclosure, examples of methods for measuring the average particle size of the specific composite particles include a method in which a sample electrode is prepared, embedded in epoxy resin, mirror-polished, and the electrode cross section is observed with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"), and a method in which an electrode cross section is prepared using an ion milling device (e.g., Hitachi High-Technologies Corporation, "E-3500") and measured with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"). In this case, the average particle size is the median value of the particle sizes of 100 particles arbitrarily selected from the specific composite particles.

[0038] (Particle size distribution D90 / D10) The particle size distribution D90 / D10 of the specific composite particles in the negative electrode material is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less. When the particle size distribution D90 / D10 of the specific composite particles is 5.0 or less, it is thought that the path of the electrolyte is easily maintained well, and the injectability of the electrolyte is maintained well. The particle size distribution D90 / D10 of the specific composite particles may be 2.0 or more. From the above viewpoint, the particle size distribution D90 / D10 of the specific composite particles is preferably 2.0 to 5.0, more preferably 2.0 to 4.0, and even more preferably 2.0 to 3.0. In the first embodiment, the particle size distribution D90 / D10 of the specific composite particles in the negative electrode material is 2.0 to 5.0.

[0039] The particle size distribution D90 / D10 can be measured using a laser diffraction particle size distribution analyzer (for example, SALD3100, Shimadzu Corporation).

[0040] When an electrode (negative electrode) is manufactured using the negative electrode material of the present disclosure, methods for measuring the particle size distribution D90 / D10 of the specific composite particles include preparing a sample electrode, embedding the electrode in epoxy resin, mirror-polishing the electrode, and observing the electrode cross section with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"); preparing an electrode cross section using an ion milling device (e.g., Hitachi High-Technologies Corporation, "E-3500") and measuring the electrode cross section with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"); etc. In this case, the particle size distribution D90 / D10 can be determined by the following method. (1) Using a binarization method or the like, the area Sn (n is the particle unique number assigned to the selected particle) of the projected particle is calculated. (2) Assuming that the particle is an ideal spherical shape, calculate the circle-equivalent diameter Ln = √Sn / π from the area Sn. (3) From the equivalent circle diameter Ln, the sphere volume Vn = (4 / 3)π(Ln) 3 Ask for. (4) Repeat steps (1) to (3) for the selected 100 particles. (5) D90 / D10 can be calculated by taking the particle diameter at the point where a distribution curve, with the vertical axis representing the cumulative percentage of the volume of 100 particles and the horizontal axis representing particle diameter, intersects with the 10% horizontal axis as the 10% diameter (D10) and the particle diameter at the point where it intersects with the 90% horizontal axis as the 90% diameter (D90).

[0041] (Standard deviation of particle size distribution) The standard deviation of the particle size distribution of the specific composite particles in the negative electrode material is preferably 0.30 or less, more preferably 0.25 or less, and even more preferably 0.20 or less. When the standard deviation of the particle size distribution is 0.30 or less, it is believed that the electrolyte path is easily maintained well, and the electrolyte injectability is maintained well. The lower limit of the standard deviation of the particle size distribution is not particularly limited. The standard deviation of the particle size distribution can be measured using a laser diffraction particle size distribution analyzer (e.g., SALD3100, Shimadzu Corporation) based on a frequency distribution graph in which the horizontal axis represents the logarithmic scale of particle diameter and the vertical axis represents the particle amount (%).

[0042] (specific surface area) The specific surface area (N2 specific surface area) of the specific composite particles determined by nitrogen adsorption measurement at 77K is 0.5m 2 / g~2.8m 2 / g, and 0.5m 2 / g~2.4m 2 / g, more preferably 0.5m 2 / g~2.2m 2 More preferably, it is 0.5m / g. 2 / g or more 2.0m 2 It is particularly preferable that the specific surface area is less than 0.5 m / g. 2 / g or more, the current density per unit area does not rise sharply, and the load is suppressed, which tends to improve the rapid charge / discharge efficiency. 2 When the SiO2 content is 1 / g or less, the interface with the electrolyte does not become too large, and decomposition of the electrolyte is suppressed, so that better high temperature resistance tends to be obtained.

[0043] Specifically, the N2 specific surface area can be determined by the BET method from an adsorption isotherm obtained by measuring nitrogen adsorption at 77 K. Specifically, the specific surface area can be determined by the method described in the Examples.

[0044] (Oil absorption amount) The oil absorption of the specific composite particles is preferably 10 mL / 100 g to 60 mL / 100 g, more preferably 15 mL / 100 g to 45 mL / 100 g, and even more preferably 20 mL / 100 g to 40 mL / 100 g. An oil absorption of 45 mL / 100 g or less is believed to indicate a small number of pores present within and on the particle surface. This is believed to result in a small interface with the electrolyte, improving storage characteristics. In addition, the small interface allows for a reduction in the amount of binder used when fabricating the negative electrode, which tends to reduce electrical resistance and improve battery performance. Furthermore, the small number of pores allows for a reduction in the amount of solvent used when drying the electrode, resulting in reduced equipment and power consumption required for drying, which is advantageous in terms of both cost and the environment of the manufacturing line. When the oil absorption is 10 mL / 100 g or more, the increase in viscosity of the slurry when kneaded with a binder or the like due to the small amount of voids between the particles tends to be suppressed. Also, the binder tends to spread favorably and kneading tends to be easier. Also, it is easier to secure voids between the particles for the movement of lithium ions.

[0045] In this disclosure, oil absorption can be measured by using linseed oil (e.g., manufactured by Kanto Chemical Co., Inc.) as the reagent liquid instead of dibutyl phthalate (DBP) as described in JIS K6217-4:2017 "Carbon black for rubber - Fundamental properties - Part 4: Determination of oil absorption." Specifically, linseed oil is titrated into the target powder using a constant-speed burette, and the change in viscosity characteristics is measured using a torque detector. The amount of linseed oil added per unit mass of the target powder corresponding to 70% of the maximum torque generated is defined as the oil absorption (mL / 100 g). For example, an absorption measurement device (product name: S-500) manufactured by Asahi Research Institute, Inc. can be used as a measuring device. Specifically, oil absorption can be determined by the method described in the Examples.

[0046] (saturated tap density) The saturated tap density of the specific composite particles is not particularly limited, and is 0.80 g / cm 3 ~1.60g / cm 3 and preferably 0.90 g / cm 3 ~1.50g / cm 3 More preferably, it is 1.00 g / cm 3 ~1.40g / cm 3 It is more preferable that:

[0047] The saturated tap density is an index of the density of the negative electrode. 3 When the saturated tap density is 1.60 g / cm or more, the compressibility when forming the negative electrode is improved, a high electrode density is achieved, and a lithium ion secondary battery with a higher capacity tends to be obtained. 3 If the particle size is less than this, there will be suitable voids between the particles, which will improve the permeability of the electrolyte, and the input / output characteristics such as rapid charge / discharge characteristics will tend to be improved.

[0048] The saturated tap density of a particular composite particle can be determined by known methods. For example, 3 Put 100 cm of sample powder into a graduated flat-bottom test tube (e.g., KRS-406 manufactured by Kuramochi Scientific Instruments Manufacturing Co., Ltd.). 3The mass (g) and volume (cm) of the sample powder after dropping it from a height of 5 cm with the stopper on were measured. 3 The number of tappings may be any number as long as the density is saturated. Specifically, the saturated tap density can be determined by the method described in the Examples.

[0049] (pressing pressure) For specific composite particles, the pressing pressure measured by the following method is 2.1 kN / cm 2 It is preferable that the strength is 2.4kN / cm or more. 2 More preferably, it is 2.7 kN / cm or more. 2 It is more preferable that the pressing pressure is 2.1 kN / cm or more. The pressing pressure can be used as one of the indicators of the hardness of the specific composite particles. 2 If the hardness of the specific composite particles is above this level, the hardness of the specific composite particles is relatively high, and even if pressure is applied during the production of the negative electrode, the electrolyte path tends to be well maintained when the battery is made. The pressure is 4.5 kN / cm 2 may be less than 4.3 kN / cm 2 may be less than 4.0 kN / cm 2 The pressing pressure may be 4.5 kN / cm or less. 2 If the hardness is not too high, the pressing pressure when preparing the negative electrode can be reduced, and the copper foil as the base is rolled, resulting in dimensional deviation or warping, which tends to prevent peeling at the interface between the active material and the current collector, resulting in a decrease in capacity, an increase in resistance, etc. Furthermore, the active material is subjected to an excessive load, which tends to prevent cracks in the crystals of the active material and an increase in the rhombohedral structure, which is a structure in which graphite crystal layers are displaced, from deteriorating in high-temperature storage characteristics. From the above viewpoint, the pressure is 2.1 kN / cm 2 ~4.5kN / cm 2 Preferably, it is 2.4 kN / cm 2 ~4.3kN / cm 2 More preferably, it is 2.7 kN / cm 2 ~4.0kN / cm 2It is more preferable that:

[0050] The pressing pressure is measured as follows: 3.0 g of the specific composite particles are filled into a mold with a diameter of 15 mm, and compressed at a constant speed of 10 mm / min using an autograph (for example, manufactured by Shimadzu Corporation). During this compression, the distance from the bottom surface of the negative electrode material to the pressing surface is measured, and this is multiplied by the bottom area of ​​the mold (for example, 1.767 cm). 2 The density under pressure is calculated from the volume of the negative electrode material obtained by multiplying the density by 1.8 g / cm. The Autograph press hammer is equipped with a load cell and is pressed at a predetermined density of 1.8 g / cm. 3 The applied pressure (kN / cm 2 Specifically, the pressing pressure can be determined by the method described in the examples.

[0051] (Springback amount) The springback amount of the specific composite particles, measured by the following method, is preferably 40% or more, more preferably 45% or more, and even more preferably 50% or more. The springback amount is an index of the elasticity of the specific composite particles, and the larger the value, the more elastic the specific composite particles. Therefore, a springback amount of 40% or more is preferable because the specific composite material has appropriate elasticity and easily returns to its original shape even when pressed during negative electrode production.

[0052] The springback amount is determined by dividing the specific composite particles into particles having a density of 1.8 g / cm 3 After compressing it to a density of 1.8 g / cm, the pressure is released. 3 The absolute value of the difference between the density of the specific composite particle after pressure release and the density of the specific composite particle after pressure release is 1.8 g / cm 3 Specifically, 3.0 g of the specific composite particles are filled into a mold having a diameter of 15 mm, and the specific composite particles are measured at a constant speed of 10 mm / min using an autograph (for example, manufactured by Shimadzu Corporation) until the density of the specific composite particles reaches 1.8 g / cm. 3 (standard density). After that, the pressure is released and the density is 1.8 g / cm 3The absolute value of the difference between the density of the composite particles after pressure release and the density of the composite particles after pressure release was calculated as 1.8 g / cm 3 Specifically, the amount of springback can be determined by the method described in the examples.

[0053] (Rhombohedral structure peak intensity ratio) In the specific composite particles, the intensity ratio (P1 / P2, also referred to as the rhombohedral structure peak intensity ratio) between the diffraction peak (P1) of the (101) plane of the rhombohedral crystal structure and the diffraction peak (P2) of the (101) plane of the hexagonal crystal structure in the X-ray diffraction pattern using CuKα radiation may be 0.15 or less, 0.10 or less, or 0.05 or less. The peak intensity ratio (P1 / P2) is preferably in a range that cannot be observed by the following method. When the peak intensity ratio (P1 / P2) is 0.15 or less, the degree of graphitization of the negative electrode material for lithium ion secondary batteries tends to be higher, and the charge / discharge capacity tends to be higher.

[0054] The rhombohedral structure peak intensity ratio can be calculated from the intensity ratio of the diffraction line of the rhombohedral structure (P1: diffraction angle 43.2°) to the diffraction line of the hexagonal structure (P2: diffraction angle 44.3°) in an X-ray diffraction pattern using CuKα radiation. Here, the diffraction angle is expressed as 2θ (θ is the Bragg angle), and the diffraction line of the (101) plane of the rhombohedral structure appears at a diffraction angle of 43.2°, and the diffraction line of the (101) plane of the hexagonal structure appears at a diffraction angle of 44.3°. The rhombohedral structure peak intensity ratio can be adjusted by adjusting the degree of graphitization (for example, adjusting the heat treatment temperature), by graphitizing the specific composite particles at a predetermined bulk density in the production process and not performing molding such as blocking before graphitization or crushing after graphitization, or by graphitizing the particles after molding but crushing them with a weak force.

[0055] (Graphitization degree) The degree of graphitization of the specific composite particles, as determined by X-ray diffraction, is preferably 93.0% to 98.0% or less, more preferably 93.5% to 97.0% or less, and may be 94.0% to 96.0% or less. When the degree of graphitization is 98.0% or less, the hardness of the specific composite particles tends to be high, and as a result, the particles tend to be elastic and less likely to be crushed even when pressure is applied. Therefore, the injectability of the electrolyte tends to be more favorably maintained. When the degree of graphitization is 93.0% or more, the discharge capacity tends to be excellent.

[0056] The graphitization degree can be determined, for example, as follows. Sixty parts by mass of the specific composite particles and 40 parts by mass of silicon powder (e.g., Fujifilm Wako Pure Chemical Industries, Ltd., purity 99.9%) are mixed in an agate mortar for 5 minutes, and the resulting mixture is placed in an X-ray diffraction measurement cell. Using an X-ray diffraction measurement device (e.g., Rigaku Corporation's X-ray Diffraction Meter MultiFlex), the diffraction angles corresponding to the graphite (002) plane and the silicon (111) plane are measured by X-ray diffraction measurement (2θ = 25° to 29°) using CuKα radiation. The theoretical diffraction angle of Si (2θ=28.442°) is used to correct the observed diffraction angles of silicon and graphite to determine the correct diffraction angle of graphite. The interplanar spacing (Å) of the d(002) plane of the negative electrode material is calculated using Bragg's equation (2d sinθ=nλ), and the degree of graphitization is calculated using the following formula. Degree of graphitization = [(3.44 - interplanar spacing) / (0.086)] x 100

[0057] (Average spacing (d 002 )) The average interplanar spacing (d 002 The average interplanar spacing (d 002The theoretical value of the average interplanar spacing (d 002 ) is 0.33557 nm or more, graphitization is not too advanced and the particles are relatively hard, so even if pressure is applied during the production of the negative electrode, the electrolyte path tends to be well maintained. From the viewpoint of the initial charge / discharge efficiency and energy density of lithium-ion secondary batteries, the average interplanar spacing (d 002 ) is preferably 0.33600 nm or less, more preferably 0.33596 nm or less, and even more preferably 0.33592 nm or less. From the above viewpoint, the average interplanar spacing (d 002 ) is preferably 0.33557 nm to 0.33600 nm, more preferably 0.33566 nm to 0.33596 nm, and even more preferably 0.33574 nm to 0.33592 nm.

[0058] Average spacing (d 002 The average interplanar spacing (d) can be calculated using the Bragg equation based on the diffraction peak corresponding to the carbon 002 plane, which appears at a diffraction angle 2θ of approximately 24° to 27° in the diffraction profile obtained by irradiating a sample with X-rays (CuKα rays) and measuring the diffraction rays with a goniometer. 002 ) can be measured under the following conditions: Radiation source: CuKα radiation (wavelength = 0.15418nm) Output: 40kV, 20mA Sampling width: 0.010° Scanning range: 10°~35° Scan speed: 0.5° / min

[0059] Bragg's equation: 2d sinθ=nλ Here, d is the length of one period, θ is the diffraction angle, n is the order of reflection, and λ is the X-ray wavelength.

[0060] The average interplanar spacing (d 002The value of the average interplanar spacing (d 002 ) can be controlled.

[0061] (Raman measurement R value) In the specific composite particles, the R value of Raman measurement (hereinafter also referred to as R value) is not particularly limited. In one embodiment, when the specific composite particles are composite particles that do not have low-crystalline carbon disposed on the surface, the R value is preferably 0.20 or less, and from the viewpoint of high durability, it is preferably 0.15 or less, and more preferably 0.10 or less. The R value may be 0.03 or more, 0.04 or more, or 0.05 or more. When the R value is 0.03 or more, lithium ions are easily inserted into the graphite crystals, which tends to improve charging characteristics and also tends to suppress the generation of lithium dendrites.

[0062] In a further embodiment, when the specific composite particles are composite particles having low-crystalline carbon disposed on at least a portion of the surface, the R value is preferably 0.50 or less, and from the viewpoint of high-temperature durability, the R value is more preferably 0.40 or less, and even more preferably 0.30 or less. In this case, the R value may be in the range of 0.20 to 0.50, or may be in the range of 0.20 to 0.40, or may be in the range of 0.20 to 0.30. When the R value is in the range of 0.20 to 0.50, lithium ions are easily desolvated, and there are many lithium insertion ports, which tends to improve low-temperature charging characteristics.

[0063] Conventional particles, such as those in which low-crystalline carbon is disposed on the surface of spherical natural graphite, have a surface that is covered with a relatively large amount of intraparticle void space, and are therefore prone to being crushed when pressed due to the intraparticle void space being compressed. This deformation also causes cracks in the coating layer (i.e., the surface low-crystalline carbon layer), making it easy for the core graphite to be exposed. On the other hand, specific composite particles, which have relatively little interparticle void space, are compressed during pressing, making it less likely for cracks to occur in the coating layer. As a result, the specific surface area of ​​the exposed particles is reduced, and the interface with the electrolyte is reduced, reducing the effect of the electrolyte. When the specific composite particles are composite particles in which low-crystalline carbon is disposed on at least a portion of the surface, the R-value is preferably 0.30 or less, taking into account the increase in R-value due to pressing.

[0064] The R value of the Raman measurement can be determined by the method described above.

[0065] When the negative electrode material of the present disclosure is a mixture of specific composite particles and particles other than the specific composite particles, the details of the average particle size, particle size distribution D90 / D10, standard deviation of particle size distribution, specific surface area, oil absorption, saturated tap density, pressing pressure, springback amount, rhombohedral structure peak intensity ratio, degree of graphitization, average interplanar spacing (d002), and R value of Raman measurement for the above-mentioned specific composite particles can be similarly applied to the properties of the entire negative electrode material.

[0066] <Method for manufacturing negative electrode material> In one embodiment, a method for producing a negative electrode material according to the present disclosure includes: (A) mixing a plurality of flat graphitizable aggregates with a binder to obtain a mixture; (B) processing the mixture to produce secondary particles having a structure in which the plurality of flat graphitizable aggregates are stacked; (C) graphitizing the secondary particles to obtain composite particles (specific composite particles) having a structure in which a plurality of flat graphite particles are stacked; Contains, in this order: The method for producing an anode material according to the present disclosure may be used to produce the aforementioned anode material for lithium ion secondary batteries. The details of the anode material produced by the method for producing an anode material according to the present disclosure can be the same as those described above for the anode material for lithium ion secondary batteries.

[0067] In a further embodiment, the method for producing a negative electrode material may include a step of classifying the plurality of flat graphitizable aggregates to remove at least one selected from the group consisting of fine particles and coarse particles before the step of obtaining a mixture in step (A). By classifying the graphitizable aggregate to remove fine particles before compounding the primary particles, a dense layered structure of the specific composite particles is formed, which tends to reduce the specific surface area.

[0068] In a further embodiment, the method for producing a negative electrode material may include, after the step of obtaining composite particles in step (C), a step of classifying the composite particles to remove at least one selected from the group consisting of fine particles and coarse particles. It is believed that classification of the specific composite particles reduces variation in particle size of the specific composite particles and can better maintain the path of the electrolyte.

[0069] Therefore, in one preferred embodiment, the method for producing the negative electrode material includes the steps of: (a) optionally classifying a plurality of flat graphitizable aggregates to remove at least one selected from the group consisting of fine particles and coarse particles; (b) mixing a plurality of flat graphitizable aggregates with a binder to obtain a mixture; (c) processing the mixture to produce secondary particles having a structure in which the plurality of flat graphitizable aggregates are stacked; (d) graphitizing the secondary particles to obtain composite particles (specific composite particles) having a structure in which a plurality of flat graphite particles are stacked; (e) optionally classifying the composite particles to remove at least one selected from the group consisting of fine particles and coarse particles; Contains, in this order:

[0070] In this disclosure, "fine particles" refers to particles having a smaller particle size than the particles recovered by classification, and "coarse particles" refers to particles having a larger particle size than the particles recovered by classification.

[0071] Hereinafter, each step that may be included in the method for producing the negative electrode material of the present disclosure will be described in detail.

[0072] [(a) Classifying a plurality of flat graphitizable aggregates to remove at least one selected from the group consisting of fine particles and coarse particles] The plurality of flat graphitizable aggregates may be classified before being composited to remove at least one selected from the group consisting of fine particles and coarse particles. By removing at least one selected from the group consisting of fine particles and coarse particles from the aggregate, a dense layered structure is formed in the composite particles, and the specific surface area tends to be reduced. By classification, the particle size distribution D90 / D10 of the plurality of flat graphitizable aggregates may be adjusted to be within the aforementioned range, for example, 2.0 to 4.4, preferably 2.0 to 4.0, and more preferably 2.0 to 3.5.

[0073] The graphitizable aggregate is not particularly limited as long as it is a flat particle, and examples thereof include petroleum-based or coal-based cokes such as fluid coke, needle coke, and mosaic coke. For example, needle coke has high crystallinity, which makes it easy to obtain flat particles and laminated particles. Furthermore, needle coke has high crystallinity, which results in large particles, making it easy to adjust the particle size by pulverization and classification. If it is desired to obtain graphite with high charging characteristics and lower crystallinity, semi-needle or mosaic coke, which is closer to a mosaic coke, may be used. In this case, fine and coarse particles tend to be generated, so it is preferable to thoroughly remove the fine and coarse particles by classification adjustment.

[0074] In the classification, it is preferable to remove fine particles having a particle size of 1 μm or less, more preferably to remove fine particles having a particle size of 2 μm or less, and even more preferably to remove fine particles having a particle size of 3 μm or less.

[0075] In the classification, it is preferable to remove coarse particles having a particle size of 60 μm or more, more preferably 50 μm or more, and even more preferably 40 μm or more. The removed coarse particles may be crushed and reused as raw material.

[0076] The classification method is not particularly limited, and examples thereof include classification using a sieve, classification using an airflow centrifugal separator, and a precision airflow classifier utilizing the Coanda effect.

[0077] (b) mixing a plurality of flat graphitizable aggregates with a binder to obtain a mixture; The binder used may be a graphitizable binder, and examples of the binder include coal-based, petroleum-based, and artificial pitch and tar, thermoplastic resins, and thermosetting resins. If necessary, a graphitization catalyst, a fluidity imparting agent, etc. may be added. Examples of graphitization catalysts include substances having graphitization catalytic activity such as silicon, iron, nickel, titanium, boron, vanadium, and aluminum, as well as carbides, oxides, and nitrides of these substances, and micaceous clay minerals.

[0078] The content of the graphitization catalyst is not limited as long as the target product can be obtained. From the viewpoint of preventing excessive graphitization, it is preferable to not add a graphitization catalyst or to add a reduced amount. For example, when the graphitization catalyst is silicon carbide (SiC), the content of silicon carbide is preferably 5% by mass or less, and more preferably 3% by mass or less, based on the mass of the graphitizable aggregate.

[0079] The mixing method is not particularly limited. From the viewpoint of reducing the amount of pores in the secondary particles, a mixing method that applies as little shear force as possible, such as a mixing method using a kiln mixer or a huddle mixer, is preferred. It is preferable not to use a kneader or the like that involves kneading, which is called a kneader.

[0080] [(c) processing the mixture to produce secondary particles having a structure in which a plurality of flat graphitizable aggregates are stacked] The method for processing the mixture is not particularly limited. In one embodiment, the mixture may be processed by heating it to volatilize the volatile components of the binder. The heating temperature is preferably 400°C or less. When the heating temperature is 400°C or less, fine holes are less likely to be formed due to oxidative combustion, making it easier to obtain particles with a small specific surface area. In this case, heating the mixture while fluidizing it with a stirrer or the like facilitates favorable granulation.

[0081] The pressure in the atmosphere may be reduced when the mixture is heated. By reducing the pressure in the atmosphere, the binder is more likely to be impregnated into the graphitizable aggregate, the gaps within the particles are filled, and stacked particles with fewer internal pores tend to be obtained.

[0082] A specific example of a method for producing secondary particles will be described below. A mixture of graphitizable aggregate and binder is stirred and mixed at a temperature above the softening point of the binder, preferably in the temperature range where the volatile components volatilize, over a period of time until the volatile components are removed. Slow degassing before graphitization (sintering) reduces the generation of bubbles during sintering of the crystals, resulting in particles with fewer pores both within and on the particle surface, which tends to result in a structure with a hard surface, a low specific surface area, and excellent high-temperature resistance. To prevent ignition of volatile gases, it is preferable to inject an inert gas such as nitrogen into the mixer to keep the oxygen concentration below 15%, which is safe. Furthermore, a temperature of 400°C or below within the mixer is preferable, as this reduces the risk of micropores being created by oxidative combustion and facilitates the production of particles with a small specific surface area. Furthermore, when pitch is used as a binder, oxygen from the atmosphere can be absorbed into the pitch to make it infusible. This improves crystal development during graphitization, resulting in a denser, more highly crystalline structure. When the degassing, infusibilization and reduced pressure treatment are carried out in an environment where the fluidity of the liquid phase or gas phase in which the binder component is softened is ensured, a greater effect tends to be obtained.

[0083] [(d) Step of graphitizing the secondary particles to obtain composite particles (specific composite particles) having a structure in which a plurality of flat graphite particles are stacked] In this step, the obtained secondary particles are graphitized. This graphitizes the graphitizable components in the secondary particles. Graphitization is preferably performed in an atmosphere where the mixture is unlikely to oxidize, such as by heating in a nitrogen atmosphere or argon gas. The graphitization temperature is not particularly limited as long as it is a temperature at which the graphitizable components can be graphitized. For example, it may be 2000°C or higher, 2500°C or higher, 2800°C or higher, or 3000°C or higher. The upper limit of the temperature is not particularly limited as long as the graphite does not sublimate, and may be, for example, 3200°C or lower. A temperature of 2000°C or higher causes a change in the crystal structure. A temperature of 2500°C or higher favorably develops the graphite crystal structure, while a temperature of 2800°C or higher favorably develops high-capacity graphite crystals capable of occluding more lithium ions. This tends to reduce the amount of graphitization catalyst remaining after calcination, thereby suppressing an increase in the ash content. In either case, the charge / discharge capacity and battery cycle characteristics tend to be improved. On the other hand, if the temperature during graphitization is 3200° C. or lower, sublimation of part of the graphite can be suppressed.

[0084] In this step, the graphitization degree may be adjusted to 98.0% or less, preferably 97.0% or less, and more preferably 96.0% or less.

[0085] The method for producing a negative electrode material according to the present disclosure may include a step of molding the secondary particles before graphitization, and a step of crushing the molded body after graphitization. By molding the secondary particles, the bulk density increases, which increases the loading capacity of the graphitization furnace, improving energy efficiency and enabling energy-saving graphitization. The molding method is not particularly limited, and for example, the secondary particles may be placed in a container such as a mold and pressurized. On the other hand, it is also preferable that the method for producing the negative electrode material of the present disclosure does not include a step of forming secondary particles before graphitization. The method for producing the negative electrode material of the present disclosure does not include a step of forming secondary particles before graphitization, and therefore preferably does not include a step of pulverizing the compact. This is thought to suppress the increase in rhombohedral crystals during the molding and pulverization processes, such as blocking, and to more suitably improve high-temperature resistance.

[0086] The bulk density of the secondary particles when subjected to graphitization (i.e., immediately before being subjected to graphitization) is 0.4 g / cm 3 ~1.0g / cm 3 and preferably 0.6 g / cm 3 ~1.0g / cm 3 More preferably, it is 0.8 g / cm 3 ~1.0g / cm 3 It is more preferable that the bulk density of the secondary particles before graphitization is 0.4 g / cm 3 If the bulk density of the secondary particles before graphitization is 1.0 g / cm or more, the number of voids in the particles is relatively small, and therefore high-density composite particles tend to be obtained even after graphitization. 3 If the temperature is below this level, when forming into blocks or the like and crushing are carried out, crushing can be carried out with a weak force, and an increase in rhombohedral crystals tends to be suppressed.

[0087] In the present disclosure, the bulk density of particles can be determined by gravimetry. That is, the bulk density of particles can be determined by dividing the mass of the particles in air by the bulk volume. Here, the mass of the particles is the mass excluding the graphitization catalyst (for example, when the secondary particles are mixed particles of an aggregate, a binder, and a graphitization catalyst, the total mass excluding the volatile components of the aggregate and the binder).

[0088] [(e) Classifying the composite particles to remove at least one selected from the group consisting of fine particles and coarse particles] The obtained composite particles may be classified to remove at least one selected from the group consisting of fine particles and coarse particles. This is thought to make the particle size of the composite particles uniform and more favorably maintain the path of the electrolyte. By classification, the particle size distribution D90 / D10 of the composite particles may be adjusted to the aforementioned range, for example, 2.0 to 5.0, preferably 2.0 to 4.0, and more preferably 2.0 to 3.0.

[0089] The classification method is not particularly limited, and examples thereof include classification using a sieve, classification using an airflow centrifugal separator, and a precision airflow classifier utilizing the Coanda effect.

[0090] When removing fine particles in this step, it is preferable to remove fine particles having a particle size of, for example, 1 μm or less, more preferably 2 μm or less, and even more preferably 3 μm or less. When removing coarse particles in this step, it is preferable to remove coarse particles having a particle size of, for example, 60 μm or more, more preferably 50 μm or more, and even more preferably 40 μm or more.

[0091] [Other steps] The method for producing the negative electrode material of the present disclosure may include steps other than the steps described above. For example, the method for producing the negative electrode material may include a step of attaching an organic compound to the surface of the secondary particles after graphitization and then performing a heat treatment. By attaching the organic compound to the surface of the secondary particles and performing the heat treatment, the organic compound attached to the surface is converted into low-crystalline carbon. This allows the low-crystalline carbon to be disposed on at least a portion of the surface of the composite particle.

[0092] The method for attaching an organic compound to the surface of secondary particles is not particularly limited, and examples thereof include a wet method in which secondary particles are dispersed and mixed in a mixed solution in which an organic compound is dissolved or dispersed in a solvent, and then the solvent is removed to attach the secondary particles; and a dry method in which mechanical energy is applied to a mixture obtained by mixing secondary particles and a solid organic compound to attach the secondary particles.

[0093] The organic compound is not particularly limited as long as it is a compound (carbon precursor) that can be converted into low-crystalline carbon by heat treatment. Examples include petroleum pitch, naphthalene, anthracene, phenanthroline, coal tar, phenolic resin, polyvinyl alcohol, etc. One type of organic compound may be used alone, or two or more types may be used in combination.

[0094] The heat treatment temperature when the secondary particles having an organic compound attached to their surfaces are heat treated is not particularly limited as long as the organic compound attached to the surfaces of the secondary particles is converted into low-crystalline carbon, and is preferably, for example, 400° C. to 1500° C. The heat treatment is preferably carried out in an inert gas atmosphere such as a nitrogen atmosphere.

[0095] As described above, the specific composite particles contained in the negative electrode material of the present disclosure do not need to have low-crystalline carbon disposed on their surfaces, and therefore the method for producing the negative electrode material of the present disclosure does not need to include the step of adhering an organic compound to the surfaces of the secondary particles after graphitization and then performing a heat treatment.

[0096] <Negative electrode for lithium-ion secondary batteries> The negative electrode for a lithium ion secondary battery of the present disclosure includes a negative electrode material layer containing the negative electrode material for a lithium ion secondary battery of the present disclosure and a current collector. The negative electrode for a lithium ion secondary battery may include other components as necessary in addition to the negative electrode material layer containing the negative electrode material for a lithium ion secondary battery of the present disclosure and the current collector.

[0097] The negative electrode for a lithium ion secondary battery can be produced, for example, by kneading a negative electrode material for a lithium ion secondary battery and a binder together with a solvent to prepare a slurry-like negative electrode material composition for a lithium ion secondary battery, and then applying this to a current collector to form a negative electrode material layer, or by forming the negative electrode material composition for a lithium ion secondary battery into a shape such as a sheet or pellet and integrating this with a current collector. Kneading can be carried out using a dispersing device such as a dispersing mixer or a planetary kneader.

[0098] The binder used in preparing the negative electrode material composition for lithium ion secondary batteries is not particularly limited. Examples of binders include styrene-butadiene copolymer (SBR), homopolymers or copolymers of ethylenically unsaturated carboxylic acid esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate, and ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid, and polymeric compounds with high ionic conductivity such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, and polymethacrylonitrile. When the negative electrode material composition for lithium ion secondary batteries contains a binder, the content of the binder is not particularly limited. For example, it may be 0.5 to 20 parts by mass per 100 parts by mass of the total of the negative electrode material for lithium ion secondary batteries and the binder.

[0099] The negative electrode material composition for lithium ion secondary batteries may contain a thickener. Examples of the thickener that can be used include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid or a salt thereof, oxidized starch, phosphated starch, and casein. When the negative electrode material composition for lithium ion secondary batteries contains a thickener, the content of the thickener is not particularly limited. For example, the content may be 0.1 to 5 parts by mass per 100 parts by mass of the negative electrode material for lithium ion secondary batteries.

[0100] The negative electrode material composition for lithium ion secondary batteries may contain a conductive auxiliary material. Examples of the conductive auxiliary material include carbon materials such as carbon black, graphite, and acetylene black, and inorganic compounds such as conductive oxides and conductive nitrides. When the negative electrode material composition for lithium ion secondary batteries contains a conductive auxiliary material, the content of the conductive auxiliary material is not particularly limited. For example, it may be 0.5 to 15 parts by mass per 100 parts by mass of the negative electrode material for lithium ion secondary batteries.

[0101] The material of the current collector is not particularly limited and can be selected from aluminum, copper, nickel, titanium, stainless steel, etc. The state of the current collector is not particularly limited and can be selected from foil, perforated foil, mesh, etc. Porous materials such as porous metal (foam metal), carbon paper, etc. can also be used as the current collector.

[0102] When the negative electrode material composition for lithium ion secondary batteries is applied to a current collector to form a negative electrode material layer, the method is not particularly limited, and known methods such as metal mask printing, electrostatic coating, dip coating, spray coating, roll coating, doctor blade coating, comma coating, gravure coating, and screen printing can be used. After the negative electrode material composition for lithium ion secondary batteries is applied to the current collector, the solvent contained in the negative electrode material composition for lithium ion secondary batteries is removed by drying. Drying can be performed using, for example, a hot air dryer, an infrared dryer, or a combination of these devices. If necessary, the negative electrode material layer may be subjected to a rolling treatment. The rolling treatment can be performed using a plate press, a calendar roll, or the like.

[0103] When the negative electrode material composition for lithium ion secondary batteries formed into a shape such as a sheet or pellet is integrated with a current collector to form a negative electrode material layer, the integration method is not particularly limited. For example, it can be performed by rolling, flat pressing, or a combination of these means. The pressure when integrating the negative electrode material composition for lithium ion secondary batteries with the current collector is preferably, for example, about 1 MPa to 200 MPa.

[0104] The negative electrode density of the negative electrode material layer is not particularly limited. For example, it is 1.1 g / cm 3 ~1.8g / cm 3 and preferably 1.1 g / cm 3 ~1.7g / cm 3 More preferably, it is 1.1 g / cm 3 ~1.6g / cm 3 It is more preferable that the negative electrode density is 1.1 g / cm 3 By setting the density to 1.8 g / cm or more, the increase in electrical resistance is suppressed and the capacity tends to increase.3 By setting the above, deterioration of input characteristics and cycle characteristics tends to be suppressed.

[0105] <Lithium-ion secondary battery> The lithium ion secondary battery of the present disclosure includes the negative electrode for a lithium ion secondary battery of the present disclosure, a positive electrode, and an electrolyte solution.

[0106] The positive electrode can be obtained by forming a positive electrode material layer on a current collector in the same manner as the negative electrode described above. The current collector can be made of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, perforated foil, mesh, or the like.

[0107] The positive electrode material used to form the positive electrode layer is not particularly limited. Examples of the positive electrode material include metal compounds (metal oxides, metal sulfides, etc.) that can dope or intercalate lithium ions, conductive polymer materials, etc. More specifically, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and their double oxides (LiCo x Ni y Mn z O2, x+y+z=1), and a double oxide containing an additional element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel-type lithium manganese oxide (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, olivine-type LiMPO4 (M: Co, Ni, Mn, Fe) and other metal compounds, conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. The positive electrode material may be one type alone or two or more types.

[0108] The electrolytic solution is not particularly limited, and for example, a solution in which a lithium salt as an electrolyte is dissolved in a non-aqueous solvent (a so-called organic electrolytic solution) can be used. Examples of lithium salts include LiClO4, LiPF6, LiAsF6, LiBF4, LiSO3CF3, etc. The lithium salts may be one type alone or two or more types. Examples of non-aqueous solvents include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propane sultone, 3-methyl sulfolane, 2,4-dimethyl sulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, triethyl phosphate, etc. The non-aqueous solvents may be used alone or in combination of two or more.

[0109] The state of the positive electrode and the negative electrode in the lithium ion secondary battery is not particularly limited. For example, the positive electrode, the negative electrode, and a separator disposed between the positive electrode and the negative electrode as needed may be spirally wound or may be stacked in the form of flat plates.

[0110] The separator is not particularly limited, and may be, for example, a resin nonwoven fabric, cloth, microporous film, or a combination thereof. Resins include those primarily composed of polyolefins such as polyethylene and polypropylene. If the structure of the lithium-ion secondary battery does not allow the positive electrode and negative electrode to come into direct contact with each other, a separator may not be required.

[0111] The shape of the lithium ion secondary battery is not particularly limited, and examples thereof include laminated type batteries, paper type batteries, button type batteries, coin type batteries, stacked type batteries, cylindrical type batteries, and prismatic type batteries.

[0112] The lithium ion secondary battery of the present disclosure has excellent input characteristics and is suitable as a large-capacity lithium ion secondary battery for use in electric vehicles, power tools, power storage devices, etc. In particular, the lithium ion secondary battery of the present disclosure has excellent high-temperature resistance and is therefore suitable as a lithium ion secondary battery for use in commercial vehicles such as buses and parcel delivery vehicles. [Example]

[0113] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0114] <<Preparation of negative electrode material>> Example 1 A so-called needle-type petroleum-derived coke (needle coke) was selected, which had a sulfur content of 0.5% by mass or less, a nitrogen content of 0.5% by mass or less, and a fixed carbon content of 98% by mass or more. When the particle cross section was observed under a polarized microscope, a needle-like striped pattern was observed throughout the entire particle. The coarsely crushed material was sieved using a 3 mm mesh sieve, and the remaining material was sieved using a 1 mm mesh sieve to recover granules with a particle size of 1 mm to 3 mm. The resulting granules were then ground in a roller mill to obtain particles with an average particle size of 200 μm.

[0115] A counter jet mill was used, and the grinding pressure was 6 kgf / cm 2 The particles obtained by applying a pressure of 0.1 MPa were pulverized, and the coarse powder was removed at a classification rotation speed of 900 revolutions per minute (rpm), yielding a pulverized powder with a particle diameter D90 of 23 μm or less. The particles were then classified using a high-speed swirling air classifier to obtain a particle diameter D10 of 7 μm or more, yielding flat coke particles, which are graphitizable aggregate. The volume particle size distribution of the obtained flat coke particles was measured, and it was confirmed that the D10 was 7 μm and the D90 was 23 μm.

[0116] A mixture was obtained by uniformly mixing 90% by mass of the obtained flat coke particles with 10% by mass of coal tar pitch (softening point 100-150°C, quinoline insolubles 15% by mass or less, fixed carbon 55-75% by mass) at room temperature. The mixture was then heated to 300-400°C under a flow of a mixed gas of dry air and nitrogen, and the pressure was reduced. During this process, the stirring blades in the mixer are moved to facilitate the discharge of gas, which tends to reduce the specific surface area. The end point of the heating and stirring was determined by utilizing the phenomenon in which low-molecular-weight gases in the coal tar pitch volatilize and the viscosity of the mixture decreases, and this was the point at which the current value of the stirring blades decreased and stabilized, and the bulk density reached 0.88 g / cm. 3 Specific granulated particles were obtained.

[0117] The granulated particles were then packed into a graphitization case and graphitized at 3100° C. The resulting particles were then sieved through a 300 mesh screen to obtain flat particle composite particles 1 of Example 1.

[0118] Example 2 Composite particles 2 of Example 2 were obtained in the same manner as in Example 1, except that the classification rotation speed of the counter jet mill was set to 1000 revolutions per minute (rpm) to remove the coarse powder portion, and then the particles were classified using a high-speed swirling air classifier to have a particle diameter D10 of 5 μm and D90 of 20 μm.

[0119] Example 3 Composite particle 3 of Example 3 was obtained in the same manner as in Example 2, except that the classification rotation speed of the counter jet mill was set to 750 revolutions per minute (rpm) to remove the coarse powder portion and obtain a pulverized powder with a particle size D10 of 7 μm and D90 of 30 μm.

[0120] Comparative Example 1 Mosaic coke (55 parts by mass) crushed to an average particle size of 15 μm, a tar pitch binder (25 parts by mass) with a softening point of 110°C, and SiC (20 parts by mass) as a catalyst were kneaded in a heated kneader at 130°C, which is the temperature at which the binder melts, to obtain a mixture of irregularly oriented flat particles. The resulting mixture was then extrusion-molded to obtain a molded product. This molded product was graphitized by heat treatment up to a maximum temperature of 2500°C or higher. The resulting graphitized product was crushed and sieved to obtain secondary graphite particles with an average particle size of 23.0 μm.

[0121] Comparative Example 2 Spherical natural graphite with an average particle size of 17 μm was prepared.

[0122] Comparative Example 3 As in Example 1, needle coke was coarsely crushed using a hammer mill. Subsequently, a flaky pulverized powder containing a large amount of fine and coarse powder was obtained by passing it through a roller mill for friction pulverization. It was confirmed that the flat particles had a D10 of 6 μm and a D90 of 55 μm, and that the cumulative volume percentage of particles with a particle size of 3 μm or less was 3% or more, indicating the presence of a large amount of fine powder (in all of Examples 1 to 3, the cumulative volume percentage of particles with a particle size of 3 μm or less was 0.1% or less). A mixture was obtained by uniformly mixing 90% by mass of these flat coke particles with 10% by mass of coal tar pitch (softening point 100°C to 150°C, quinoline insoluble matter 15% by mass or less, fixed carbon 55% by mass to 75% by mass). The mixture was then packed into a graphite case, covered, and steam-baked at 1000°C. Next, the mixture was graphitized at 3100° C., and then sieved through a 300 mesh screen to obtain flat artificial graphite particles of Comparative Example 3 having an average particle size of 27.0 μm.

[0123] The appearance and cross-section of the negative electrode materials of the Examples and Comparative Examples were observed using an electron microscope. It was confirmed that the negative electrode materials produced in Examples 1 to 3 had a structure in which flat graphite particles were stacked. It was confirmed that the negative electrode material produced in Comparative Example 1 contained particles in which multiple flat graphite particles were aggregated or bonded together so that their main surfaces were non-parallel. It was confirmed that the flat artificial graphite particles produced in Comparative Example 3 were flat (scale-like) primary particles. It was also observed that the negative electrode materials produced in Examples 1 to 3 had a smaller amount of pores than the negative electrode materials of Comparative Examples 1 and 2. Electron microscope images of the appearance and cross-section of the negative electrode material of Example 1 are shown in FIGS. 1A and 1B , those of Comparative Example 1 are shown in FIGS. 2A and 2B , those of Comparative Example 2 are shown in FIGS. 3A and 3B , and those of Comparative Example 3 are shown in FIGS. 4A and 4B , respectively. The cross-sectional image of the negative electrode material of Comparative Example 1 shown in FIG. 2B shows the negative electrode material having a density of 1.65 g / cm 3 The other microscopic images show the state of the negative electrode material without pressing.

[0124] <<Production of negative electrodes for lithium-ion secondary batteries>> The negative electrode materials (97.6 parts by mass) of the Examples and Comparative Examples, carboxymethyl cellulose (CMC) (1.2 parts by mass), and styrene-butadiene rubber (SBR) (1.2 parts by mass) were kneaded to prepare a slurry. This slurry was applied to the shiny surface of the electrolytic copper foil in an amount of 10 g / cm. 2 After pre-drying at 90°C for 2 hours, the electrode density was adjusted to 1.65 g / cm using a roll press. 3 Thereafter, a curing treatment was carried out by drying at 120° C. for 4 hours in a vacuum atmosphere, thereby obtaining a negative electrode for a lithium ion secondary battery.

[0125] <<Production of lithium-ion secondary batteries>> A coin cell was fabricated using the electrode obtained above as the negative electrode, metallic lithium as the counter electrode, a mixed solution of ethylene carbonate / ethyl methyl carbonate (3:7 volume ratio) containing 1 M LiPF6 and vinylene carbonate (VC) (1.0 mass%) as the electrolyte, a 25 μm thick polyethylene microporous membrane as the separator, and a 250 μm thick copper plate as the spacer.

[0126] <Evaluation of negative electrode materials and battery characteristics> The properties of the negative electrode materials obtained in the examples and comparative examples, and the properties of the negative electrodes and lithium ion secondary batteries produced using the negative electrode materials were measured by the following methods.

[0127] [Average particle size, particle size distribution D90 / D10, and standard deviation of particle size distribution] Using a laser diffraction particle size analyzer (SALD3100, Shimadzu Corporation), the average particle size of the primary particles and negative electrode material was determined as the particle size (D50) at which the cumulative total from the small diameter side in the volumetric particle size distribution is 50%. Furthermore, the particle size distribution D90 / D10, which represents the ratio of the particle size (D90) at which the cumulative total from the small diameter side in the volumetric particle size distribution is 90% to the particle size (D10) at which the cumulative total from the small diameter side is 10%, was determined for the primary particles and negative electrode material. The standard deviation of the particle size distribution was also calculated using the method described above.

[0128] [Specific surface area] The negative electrode material was filled into a measurement cell and pre-treated by heating at 200°C while being degassed under vacuum. Nitrogen gas was adsorbed into the sample using a gas adsorption apparatus (ASAP2010, manufactured by Shimadzu Corporation). The obtained sample was subjected to BET analysis using the five-point method to determine the specific surface area.

[0129] [Oil absorption amount] Using an absorption measurement device (S-500, Asahi Research Institute Co., Ltd.), linseed oil was titrated into 30 g of anode material using a constant-speed burette, and the change in viscosity characteristics was measured using a torque detector. The amount of linseed oil added per 100 g of anode material corresponding to 70% of the maximum torque generated was defined as the oil absorption (mL / 100 g).

[0130] [Saturated tap density] Capacity 150cm 3 100 cm of anode material was placed in a graduated flat-bottom test tube (Kuramochi Scientific Instruments Manufacturing Co., Ltd., KRS-406). 3 The mass (g) and volume (cm) of the negative electrode material after dropping it from a height of 5 cm with the stopper on 3 The saturated tap density was calculated from the tapping time. The tapping was continued until the density was saturated.

[0131] [Press pressure] 3.0 g of negative electrode material was filled into a 15 mm diameter mold and compressed at a constant rate of 10 mm / min using an Autograph (Shimadzu Corporation). During this compression, the distance from the bottom of the negative electrode material to the press surface was measured, and this was multiplied by the bottom area of ​​the mold to obtain the volume of the negative electrode material, from which the density during compression was calculated. A load cell was attached to the Autograph press hammer, and the specified density of 1.8 g / cm was calculated. 3 The applied pressure (kN / cm 2 ) was the pressing pressure.

[0132] [Springback amount] When pressed using the above method using an Autograph (Shimadzu Corporation), the standard density was 1.8 g / cm 3 The absolute value of the difference between the density of the negative electrode material after springback and the density of the negative electrode material after springback is 1.8 g / cm 3 The amount of springback was calculated by dividing the value by .

[0133] [Rhombohedral structure peak intensity ratio] The rhombohedral structure peak intensity ratio (P1 / P2) was calculated from the intensity ratio of the diffraction line of the rhombohedral structure (P1: diffraction angle 43.2 degrees) to the diffraction line of the hexagonal structure (P2: diffraction angle 44.3 degrees) in the X-ray diffraction pattern using CuKα radiation.

[0134] [Graphitization degree] The degree of graphitization was measured by the above-mentioned method using an X-ray diffraction measuring device (X-RAY DIFFRACTIOMETER MultiFlex, Rigaku Corporation).

[0135] [Average spacing (d 002 ) The sample is irradiated with X-rays (CuKα rays), and the diffraction profile is measured using a goniometer. The diffraction peak corresponding to the carbon 002 plane appears at a diffraction angle 2θ of 24° to 27°. Based on this, the average interplanar spacing (d 002 ) was calculated. 002 ) was measured under the following conditions: Radiation source: CuKα ray (wavelength=0.15418nm) Output: 40kV, 20mA Sampling width: 0.010° Scanning range: 10°~35° Scan speed: 0.5° / min

[0136] Bragg's equation: 2d sinθ=nλ Here, d is the length of one period, θ is the diffraction angle, n is the order of reflection, and λ is the X-ray wavelength.

[0137] [Raman measurement R value] The R value was measured under the following conditions using a Raman spectrometer (NSR-1000 model, manufactured by JASCO Corporation). Laser wavelength: 532nm Irradiation intensity: 1.5mW (measured by laser power monitor) Measurement range: 830cm -1 ~1940cm -1 Irradiation time: 60 seconds ·Irradiation area: 4μm 2 Baseline: 1050cm -1 ~1750cm -1

[0138] [Evaluation of high-temperature storage maintenance rate and high-temperature storage recovery rate] The fabricated lithium-ion secondary battery was placed in a thermostatic chamber set at 25°C, and the current was 0.2 C and the voltage was 0 V (V vs. Li / Li +), then constant voltage charging was performed at 0 V until the current value reached 0.02 C. After a 30-minute rest, the battery was charged at a current value of 0.2 C and a voltage of 1.5 V (V vs. Li / Li). + After repeating this charge / discharge twice, the current was 0.2 C and the voltage was 0 V (V vs. Li / Li). + ), and then constant voltage charging was performed at 0 V until the current value reached 0.02 C. The battery was then placed in a thermostatic chamber set at 60° C. and stored for 7 days. Then, place it in a thermostatic chamber set at 25°C and leave it for 60 minutes. Then, apply a current of 0.2 C and a voltage of 1.5 V (V vs. Li / Li + ) was discharged at a constant current. Then, charging and discharging were repeated once under the above conditions. This storage at 60°C and checking of the capacity after storage were repeated a total of three times. The high-temperature storage maintenance rate and high-temperature storage recovery rate were calculated using the following formulas. High temperature storage retention rate (%) = (first discharge capacity at 25°C after storage at 60°C for 21 days) / (second discharge capacity at 25°C before storage at 60°C) × 100 High-temperature storage recovery rate (%) = (second discharge capacity at 25°C after storage at 60°C for 21 days) / (second discharge capacity at 25°C before storage at 60°C) × 100

[0139] [Liquid injection property] Electrode density 1.65g / cm 3 The pressed negative electrode was punched into a 16mm diameter circle and attached to a glass substrate with double-sided tape to create a flat, distortion-free electrode surface. 3 μL of PC (polycarbonate, manufactured by Kishida Chemical Co., Ltd.) was dispensed onto the center of the circular electrode using a micropipette, and the time it took for the solution to penetrate was measured. Three identical electrodes were prepared, and the average values ​​of three measurements are shown in Table 1.

[0140] [Quick charging capacity maintenance rate] The negative electrode obtained above was placed on a plate with an electrode area of ​​2.00 cm. 2A 2016-type coin cell was fabricated using a cathode made of aluminum foil coated with lithium cobalt oxide, an electrolyte solution of a mixture of ethylene carbonate / ethyl methyl carbonate (3 / 7 volume ratio) containing 1.0 M LiPF6 and vinylene carbonate (0.5 mass%), a 25 μm-thick polyethylene microporous membrane as the separator, and a spring spacer as the spacer. This coin cell was used as the evaluation cell.

[0141] The fabricated evaluation cell was subjected to an aging treatment before a rapid charge test. Specifically, the evaluation cell was placed in a thermostatic chamber maintained at 25°C and charged at a constant current of 0.92 mA to 4.2 V, and then further charged at a constant voltage of 4.2 V until the current decayed to a value equivalent to 0.046 mA. After charging, a 10-minute pause was taken, followed by discharging at 0.92 mA to 2.75 V. This charge-discharge cycle was repeated five times.

[0142] A rapid charge test was conducted using the aged evaluation cell. Specifically, the evaluation cell was placed in a thermostatic chamber maintained at 25°C and charged at a constant current of 0.92 mA to 4.2 V, and the charge capacity (1) was measured. After charging, the cell was allowed to rest for 10 minutes before discharging. Discharging was continued at 4.6 mA to 2.75 V. Further, constant current charging was continued at 6.9 mA to 4.2 V, and the charge capacity (2) was measured. After charging, the cell was allowed to rest for 10 minutes before discharging at 4.6 mA to 2.75 V. The charge capacity (2) was divided by the charge capacity (1) and multiplied by 100 to obtain the rapid charge capacity retention rate (%).

[0143] The evaluation results are shown in Table 1. In Table 1, D10, D50, D90, D90 / D10, and the standard deviation of the particle size distribution are values ​​for the negative electrode material after graphitization.

[0144] [Table 1]

[0145] As shown in Table 1, when the negative electrode materials prepared in Examples 1 to 3 were used, the injection property of the negative electrode and the high temperature resistance of the lithium ion secondary battery were improved. Furthermore, when the negative electrode materials prepared in Examples 1 to 3 were used, the rapid charge capacity retention rate was also improved.

[0146] All publications, patent applications, and technical standards mentioned in this specification are incorporated by reference into this specification to the same extent as if each individual publication, patent application, or technical standard was specifically and individually indicated to be incorporated by reference.

Claims

1. Composite particles having a structure in which a plurality of flat graphite particles are stacked, The particle size distribution D90 / D10 of the plurality of flaky graphite particles is 2.0 to 4.4; The specific surface area of ​​the composite particles determined by nitrogen adsorption measurement at 77 K is 2.2 m 2 / g or less, In the composite particle, in an X-ray diffraction pattern using CuKα radiation, the intensity ratio (P1 / P2) of the diffraction peak (P1) of the (101) plane of the rhombohedral crystal structure to the diffraction peak (P2) of the (101) plane of the hexagonal crystal structure is 0.15 or less. Negative electrode material for lithium-ion secondary batteries.

2. A composite particle having a structure in which a plurality of flat graphite particles are stacked, The particle size distribution D90 / D10 of the plurality of flaky graphite particles is 2.0 to 4.4; The composite particles have a specific surface area of ​​2.2 m 2 / g or less as determined by nitrogen adsorption measurement at 77 K; the composite particles are composite particles having no low-crystalline carbon disposed on a surface thereof, The R value of the composite particle in which low-crystalline carbon is not disposed is 0.20 or less in Raman spectroscopy measurement. Negative electrode material for lithium-ion secondary batteries.

3. The negative electrode material for lithium ion secondary batteries according to claim 1 or 2, wherein the particle size distribution D90 / D10 of the composite particles is 2.0 to 5.

0.

4. The specific surface area of ​​the composite particles determined by nitrogen adsorption measurement at 77 K is 0.5 m 2 / g to 2.2 m 2 The negative electrode material for lithium ion secondary batteries according to any one of claims 1 to 3, wherein the molecular weight of the negative electrode material is 100% or more.

5. The negative electrode material for lithium ion secondary batteries according to any one of claims 1 to 4, wherein the degree of graphitization of the composite particles determined by an X-ray diffraction method is 93.0% to 98.0%.

6. the composite particles have low-crystalline carbon disposed on at least a portion of a surface thereof, The R value of the composite particles in which the low-crystalline carbon is arranged is 0.50 or less in Raman spectroscopy measurement. A negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 5 depending on claim 1.

7. The negative electrode material for lithium ion secondary batteries according to any one of claims 1 to 6, wherein the composite particles have an oil absorption of 15 mL / 100 g to 45 mL / 100 g.

8. A negative electrode for a lithium ion secondary battery comprising: a negative electrode material layer containing the negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 7; and a current collector.

9. A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to claim 8, a positive electrode, and an electrolyte solution.

10. A step of classifying a plurality of flat graphitizable aggregates to remove at least one selected from the group consisting of fine particles and coarse particles; mixing the classified flat graphitizable aggregates with a binder to obtain a mixture; processing the mixture to produce secondary particles having a structure in which the plurality of flat graphitizable aggregates are layered; A step of graphitizing the secondary particles to obtain composite particles having a structure in which a plurality of flat graphite particles are stacked; A step of classifying the composite particles to remove at least one selected from the group consisting of fine particles and coarse particles; The method for producing the negative electrode material for lithium ion secondary batteries according to any one of claims 1 to 7, comprising:

11. The bulk density of the secondary particles to be graphitized is 0.4 g / cm 3 ~1.0 g / cm 3 The method for producing a negative electrode material for a lithium ion secondary battery according to claim 10,

12. The method for producing a negative electrode material for a lithium ion secondary battery according to claim 10 or 11, wherein the processing of the mixture includes heating the mixture to volatilize a volatile component of the binder.

13. The method for producing a negative electrode material for a lithium ion secondary battery according to claim 12, further comprising reducing the pressure in the atmosphere during the heating.

Citation Information

Patent Citations

  • Process for preparing crystal nodulizing graphite

    CN1699479A

  • Graphite particle for negative electrode of nonaqueous secondary battery

    JP2003168432A

  • Negative electrode material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte battery using the same

    JP2010251315A

  • Composite graphite-based material and manufacturing method thereof, negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2013258130A

  • Graphite particle for nonaqueous secondary battery, negative electrode for nonaqueous secondary battery using the same, and nonaqueous secondary battery

    JP2014067680A